Promoting corporate social responsibility in small and medium enterprises in the Caribbean : methodology report - Shah, Kalim U. (ECLAC [Santiago]CL, 2008)
Provides a methodology for investigating CSR awareness and activity in the Caribbean region. Focuses directly on small and medium enterprises and secondarily on the other large and multinational companies that also operate in the Caribbean region.